INCREASING THE FIRST YEAR STUDENTS’ SPEAKING ABILITY BY USING PARTICIPATION POINT STRATEGY IN TEACHING ENGLISH AT SMAN 14 MAKASSAR - EKA PRATIWI SUDIRMAN; MUHAMMAD AZWAR ASSIDDIQ (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The research dealt with increasing students' speaking ability by using a participation point strategy in teaching English. Participation point strategy was used in order to improve students' speaking ability. The problem statement of this research was to find out whether the participation point strategy is effective in improving the students speaking ability or not. This study used a quasi-experimental design. The population of this research was the first-year students of SMAN 14 Makassar, which consisted of 54 students. The sample was taken using the purposive sampling technique, which consisted of 27 students of class X.1 as an experimental class and 27 students of class X.2 as a control class. It takes 12 meetings which are covered in a pre-test, treatment, and post-test. The data were taken from the speaking test in the pre-test and post-test. Based on the result of the research, it is found that after being treated with the participation point strategy, the students are encouraged to speak in their English classes. They are actively involved in oral participation during the teaching and learning process. The giving points applied in this research have succeeded in solving the students' problem in participating in oral task in their English classes. Moreover, the participation point strategy effectively increases the first-year students' speaking ability of SMAN 14 Makassar.